How to overcome barriers for innovations in organizations from the public sector – Local governments for the future - Mackiewicz, Karolina (My University, 2017)
The barriers for innovations in organizations from the public sector, particularly local administration (cities, municipalities) are of highest relevance today with strong implications for the future. Capacity for innovation is recognized as a crucial factor for the development and survival of modern organizations. Already now the public sector must compete for funding, interest and good image according to the same rules as the private companies and this trend seems to strengthen. Cities deal with large, complex problems, which require innovative thinking. The problem is the lack of capacity to generate new solutions and, as a result, there are not enough non-standard strategies and groundbreaking ideas that could help produce prospect and success. Three research questions were set for the study: 1/ What are the main barriers for innovations in the local administration? 2/ What are the main drivers for innovations in the local administration? 3/ What kind of measures would help the local organizations to reduce these barriers? The research material and data collected during interviews with administrators, policy makers and researchers were analyzed with Causal Layered Analysis (CLA) and through the lenses of the three-dimensional system (mechanic, dynamic, organic). As a result, four visions of the future of the organizations from the public sector, five systemic barriers and four drivers for innovations were extracted. The visions are: 1) Locked Tower – the system with predominant mechanistic dimension; 2) Turtle in the City, with the organic dimension present to a bigger extent than in a previous one; 3) The Ice is Cracking – with the balance between mechanistic and organic dimension, the dynamic dimension appears; 4) Open and Fearless – the system with predominant dynamic dimension – emerging but aspirational at the moment. The study revealed that the hierarchical structure, fear of mistakes, old-school managers, who control and supervise but lack trust in their employees, as well as fragmented communication and too rigorous planning (i.e. lack of flexibility) are the key barriers that should be limited or removed if the cities want to be innovative, more prosperous and successful in the future. On the other hand, there several ways in which the public sector could improve its innovativeness and competitiveness. They are: investing in human resources, encouraging the experimenting culture, supporting brave leaders with vision and commitment and promoting the division of work that allows more time for brainstorming and implementing instead of planning and reporting. In the conclusion, the study provided the diagnosis of the barriers for innovations in the organizations from the public sector, more precisely in the city administration, and a set of recommendations on how to improve the situation.